Comet parameters and plasma 8-Iso-prostaglandins F2α: Common markers of etiopathogenesis in major depression and indicators of antioxidant action of fluoxetine - Rajeev Panwar; M Sivakumar (Wolters Kluwer Medknow Publications, 2021)
Background: Major depression can be characterized by isolated episodes of disturbance in psychosomatic functions for a duration of at least two weeks along with intermediate non-symptomatic periods. The factors playing important role in the etiology of major depression were family history, genetic factors, decreased levels of serotonin and norepinephrine; increased levels of interleukins or any other medical illness having an increased cytokine production. The pathogenesis of major depression involves oxidative stress, which consists of synthesis of free radicals causing damage to nucleic acids, lipids, carbohydrates, and proteins present in the cells. Oxidative stress - induced DNA damage consists of numerous types of lesions which can be assessed by the comet assay method. Prostaglandin F2-alpha is produced because of oxidative stress-induced peroxidation of cell membrane lipids and has elevated plasma levels in patients with major depression. Fluoxetine is the drug of choice for major depression and found to have antioxidant properties. The present study was done to assess the correlation between plasma 8-iso-PGF2α levels and the comet parameters, namely comet length (CL), head diameter (HD), % of DNA in head (%DNA Head), tail length (TL) and % of DNA in tail (%DNA Tail), before starting and after finishing the eight-week fluoxetine therapy. Methodology: The prospective clinical study was conducted in the Department of Anatomy in collaboration at, Jawaharlal Institute of Postgraduate Medical Education and Research, Puducherry. The study group consisted of drug naïve, newly diagnosed major depression patients belonging to age-group of ≥ 18 to 50 years and followed up after eight weeks of fluoxetine therapy. Results: The correlation was found to be positive between the levels of 8-iso-PGF2α in the plasma and all the comet parameters except %DNA Tail, which showed a negative (inverse) relationship with the levels of 8-iso-PGF2α in the plasma. Conclusion: The current study suggested the role of oxidative stress in causing DNA damage and lipid peroxidation in major depression patients and the antioxidant role of fluoxetine in causing decrease in the levels of parameters of oxidative stress and subsequent DNA repair.